Development of Electrocardiogram (ECG) Monitoring System using IoT - Wan Haron, Wan Muhammad Azam; Adon, Mohammad Nazib (Evolution in Electrical and Electronic Engineering, 2023)
This work aims to develop and produce the design of an Electrocardiogram (ECG) system that uses IoT to facilitate the output signal data of the patient's heartbeat flow to be sent to the smartphone of the person in charge for observing the condition and health of the patient's heart, which the limitations of typical ECG systems provide only a snapshot of heart health at a specific moment and limit mobility, the solution is develop ECG system that uses IoT that enables continuous remote monitoring to get real-time normal ECG signal and comprehensive long-term assessment of a patient's heart condition. This research is to develop an electrocardiogram (ECG) device based on module AD8232, to develop and integrate IoT-based ESP8266 and to analyze ECG signal and real-time monitoring system, which uses the ECG module sensor AD8232 and use the Durian Uno with ESP8266 Wi-Fi then will view the result in Blynk application. The experiment was to observe three volunteers with different weights and heights and also different ECG lead placements. Multiple tests using the created ECG device and the laboratory ECG were used to corroborate this. In the final stage of this work, the result for the real-time signal of the ECG that develops is the same as the ECG signal of normal people. However, it was challenging to achieve these goals, which suggests in the future, some filters for the ECG signal result to get excellent output can be more accurate and relevant to use in hospitality.